Responses of Firms to Tax, Administrative and Accounting Rules: Evidence from Armenia - Zareh Asatryan; Andreas Peichl (Center for Economic Studies and ifo Institute (CESifo), 2017)
Using panel data on the full population of corporate tax returns from Armenia, we study behavioral responses of firms to three size-dependent regulations. We find: i) a strong response to an accounting notch where IFRS becomes mandatory; ii) a moderate response to an administrative notch below which the frequency of filing taxes declines; and iii) no response to the VAT registration threshold notch. Exploiting tax audits, we provide evidence suggesting that income under-reporting drives the bunching response of firms. Additional evidence suggests that firms respond to audits by compensating additional reported income by a 0.90 dollar increase in deductions.
Keywords: H25; H26; O12; 330; small and medium enterprises; size-dependent regulation; value added tax; tax administration; tax accounting; tax evasion